Factors influencing internationalisation decision of upstream-SME in Singapore : a case study on plastic engineering industry. - Lim, Kok Tiong. (2008)
The purpose of this study is set up to determine the factors influencing the decision making process of upstream-SMEs in their internationalisation process. To establish grounds for the case study, an extensive literature review was performed on the international supply chain as well as the internationalisation process of SMEs, together with an indepth study into plastic engineering industry.